An educational intervention to prevent overweight in pre-school years: a cluster randomised trial with a focus on disadvantaged families - Alison Hodgkinson; Janice Abbott; Margaret A. Hurley; Nicola Lowe; Pamela Qualter (BMC, 2019)
Abstract Background Early prevention is a promising strategy for reducing obesity in childhood, and Early Years settings are ideal venues for interventions. This work evaluated an educational intervention with the primary aim of preventing overweight and obesity in pre-school children. Methods A pragmatic, cluster randomised trial with a parallel, matched-pair design was undertaken. Interventions were targeted at both the cluster (Early Years' Centres, matched by geographical area) and individual participant level (families: mother and 2-year old child). At the cluster level, a staff training intervention used the educational resource Be Active, Eat Healthy. Policies and provision for healthy eating and physical activity were evaluated at baseline and 12-months. The intervention at participant level was the Healthy Heroes Activity Pack: delivered over 6 months by Centre staff to promote healthy eating and physical activity in a fun, interactive way. Child and parent height and weight were measured at four time-points over 2 years. The trial primary outcome was the change in BMI z-score of the child between ages 2 and 4 years. Secondary outcomes consisted of parent-reported measures administered at baseline and two-year follow-up. Results Five pairs of Early Years' Centres were recruited. Four pairs were analysed as one Centre withdrew (47 intervention families; 34 control families). At the cluster level, improvement in Centre policies and practices was similar for both groups (p = 0.830). At the participant level, the intervention group reduced their mean BMI z-score between age 2 and 4 years (p = 0.002; change difference 0.49; 95% CI 0.17 to 0.80) whereas the control group showed increasing BMI z-score throughout. Changes in parent-reported outcomes and parent BMI (p = 0.582) were similar in both groups. Conclusions The Healthy Heroes educational resource deterred excess weight gain in pre-school children from poor socioeconomic areas. With training, Early Years' staff can implement the Healthy Heroes programme. Trial registration ISRCTN22620137 Registered 21st December 2016.